Globalisasi, Kemiskinan dan Ketimpangan Global: Prioritas Keadilan dan Pentingnya Integrasi Ilmu Pengetahuan - Agus Wahyudi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2003)
The article discusses the phenomenon of globalization, poverty and global inequalities as a part of widely discussed topic of social justice. It finds that the discussion around the two phenomena has not yet reached the level of urgent priority as to find solutions and alternatives. It therefore encourages (social) sciences to recapture the topic and develops further by integrating the abstract and speculative humanities studies –especially that of political philosophy subjectâ€” with the more empirical and theoretical socio-political ones. It offers two ways of so doing: firstly, promoting the focus of study –both in political philosophy and socio-political research– on domestic and global aspiration of social justice. Secondly, exploring more on own (local and domestic) tradition to find appropriate norms and principles of social justice, i.e. to challenge those of the Western ethical tradition.